(untitled) (Baghdad Science Journal, 2021)
Sludge worm samples were collected from the Tigers River sediment during the period from November 2018 to June 2019 in Al Sarafiya District/ Baghdad- Iraq. Biometric morphological measurements focusing on the form of penis sheath and chaetal morphology were used for species identification, in addition to molecular analysis by amplification of conserved 18s rRNA encoding gene using ITS1 and ITS4 universal primers.According to the morphological measurement records, the results revealed the existence of Limnodrilus hoffmeisteri Claparede 1862, L. claparedeianus Ratzel, 1868 and L. cervix Brinkhurst 1963. Other two groups of specimens, with short penis sheath, were identified by molecular technology as L. hoffmeisteri complex, and L. claparedeianus.-cervix. Both species were considered as new record for Iraqi fauna, and had been registered in NCBI under the accession number LC497073 and LC497074 respectively According to the morphological measurements records, the results revealed the existence of Limnodrilus hoffmeisteri Claparede 1862, L. claparedeianus Ratzel, 1868 and L. cervix Brinkhurst 1963, which identified by molecular analysis using 18S rRNA gene and DNA sequencing recorded L. hoffmeisteri complex, This species is a new record in Iraq, and has been registered in NCBI under the accession number LC497073. There was also specimen identified by molecular analysis using 18S rRNA gene and DNA sequencing recorded L. Claparedeianus –cervix. Also, this species is a new record in Iraq, and has been registered in NCBI under the accession number LC497074. ــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــــ Keyword: Limnodrilus hoffmeisteri complex, Iraq, LC497073, NCBI, Limnodrilus hoffmeisteri, L. Claparedeianus, L. cervix, L. Claparedeianus –cervix, LC 497073. *Part of M.Sc. Thesis of Research Sludge worms samples were collected from the Tigers River sediment in Al Sarafiya district, / Baghdad- Iraq. Biometric morphological measurement focusing on the form of penis sheath and chaetal morphology, in addition to molecular analysis using 18s rRNA gene, were used for species identification. According to the morphological measurements records, the results revealed the existence of two groups of Limnodrilus hoffmeisteri Claparède 1862 Individuals have long penis sheath with distal end with symmetrical or asymmetrical hood, while other individuals with short penis sheath with circular plate- like hood, which identified by molecular analysis as L. hoffmeisteri complex, and the isolate 18S rRNA recorded with the accession number LC497073 Two groups of very long penis sheath identified as L. claparedeianus Ratzel, 1868, and L. cervix Brinkhurst 1963, with dorsal and ventral projections. There are also a group of specimens with short penis sheath, which identified by molecular techniques as L. Claparedeianus –cervix 18S rRNA encoding genomic sequence was resented to the NCBI, recorded with the accession number LC497074. Limnodrilus hoffmeisteri complex and L. claparedeianus – cervix were considered as new records for Iraq.